PENGARUH LEVERAGE, PROFITABILITY, DAN FAKTOR LAINNYA TERHADAP TAX AVOIDANCE - PAHALA PERDINAND NATANAEL SINAGA; ADE HANIFA PUTRI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
This study aims to analyze the influence of Leverage, Profitability, Independent Commissioner, Audit Committee, Capital Intensity, Transfer Pricing, and Company Size on Tax Avoidance practices in manufacturing companies. The research focuses on manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The sample selection in this study was conducted using the purposive sampling method. Based on the sample selection criteria, 49 companies were selected as the research sample from a total of 147 data points used in the study. The hypothesis testing in this study employed multiple regression analysis as the data analysis method. The results of the study indicate that the variables profitability and capital intensity have a positive effect on tax avoidance. Meanwhile, leverage, independent commissioners, audit committees, transfer pricing, and company size do not affect tax avoidance.